Double-blind Cross-over Trial of Flurbiprofen and Phenylbutazone in Ankylosing Spondylitis. Issue 5943 (30th November 1974) - Calin, A.; Grahame, R.
Abstract : A double-blind cross-over study in 35 patients with ankylosing spondylitis was carried out comparing flurbiprofen (150 mg daily)—a new non-steroidal anti-inflammatory agent—with phenylbutazone (300 mg daily) over a four-week period. Flurbiprofen was well tolerated and shown to have therapeutic efficacy approaching that of phenylbutazone. The results suggest that flurbiprofen may prove a valuable alternative in the treatment of ankylosing spondylitis, and longterm efficacy and tolerance studies are clearly indicated.